A chemo-rheological approach to the healing characteristics of asphalt binders under short- and long-term oxidative aging. (10th October 2019) - Wang, Chao; Chen, Yifang; Cao, Wei
Highlights: Healing mastercurves and healing rate were determined based on the LASH test. Oxidative aging exhibited negative effects on asphalt binder self-healing. SBS modifier slightly reduced the healing rate within the crack initiation phase. Presence of more light fractions (oil phases) and small molecules benefited healing. Abstract: Asphalt is known to have self-healing characteristics. This study was aimed to investigate the healing behavior of asphalt binders under short- and long-term oxidative aging conditions, and to evaluate the relationship between healing potential and chemical properties. Two asphalt binder types were evaluated which included one neat (unmodified) asphalt and one styrene-butadienestyrene (SBS) modified binder. Healing characterization was based on the recently developed linear amplitude sweep based healing (LASH) test. Chemical characterization consisted of the saturates, aromatics, resins, and asphaltenes (SARA) fractionation, and gel permeation chromatography (GPC) tests. Based on the obtained healing index from the LASH test, oxidative aging generally had negative effects on healing, and that the SBS modifier slightly reduced the healing potential within the crack initiation phase. Presence of more light fractions, small molecules, and molecules that are longer with less branches would promote the molecular self-diffusion across crack surfaces, thereby enhancing the healing process. The negative effect of oxidative aging on healing may be attributed to molecular agglomeration which results in a less dispersed structure with reduced capability of the asphalt to diffuse across crack interfaces. This study provided a preliminary validation of the LASH test and the healing index.